2016
DOI: 10.1101/gr.201574.115
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cis-regulation with a compendium of genome-wide histone H3K27ac profiles

Abstract: Model-based analysis of regulation of gene expression (MARGE) is a framework for interpreting the relationship between the H3K27ac chromatin environment and differentially expressed gene sets. The framework has three main functions: MARGE-potential, MARGE-express, and MARGE-cistrome. MARGE-potential defines a regulatory potential (RP) for each gene as the sum of H3K27ac ChIP-seq signals weighted by a function of genomic distance from the transcription start site. The MARGE framework includes a compendium of RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 72 publications
2
111
0
Order By: Relevance
“…Algorithm-based enhancer prediction models such as ChromHMM, ROSE, MARGE, and super-enhancer predictions claim to identify enhancers controlling cell identity (Ernst and Kellis 2012;Loven et al 2013;Whyte et al 2013;Wang et al 2016); however, the vast majority of these predictions remain functionally unexplored. This enhancer deletion study in ES cells revealed that, in some cases, transcriptional regulation of a single gene (Sall1, Tet1, Lifr, Jarid2) or gene cluster (Dppa5a/Ooep, Ifitm, and Six) was almost entirely dependent on the EC or isolated enhancer.…”
Section: Discussionmentioning
confidence: 99%
“…Algorithm-based enhancer prediction models such as ChromHMM, ROSE, MARGE, and super-enhancer predictions claim to identify enhancers controlling cell identity (Ernst and Kellis 2012;Loven et al 2013;Whyte et al 2013;Wang et al 2016); however, the vast majority of these predictions remain functionally unexplored. This enhancer deletion study in ES cells revealed that, in some cases, transcriptional regulation of a single gene (Sall1, Tet1, Lifr, Jarid2) or gene cluster (Dppa5a/Ooep, Ifitm, and Six) was almost entirely dependent on the EC or isolated enhancer.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, a linear or logistic regression model learns feature weights, which can identify important cis -regulatory elements for cell type specific expression. When profiling multiple cell types using a single active mark (e.g., H3K27ac), one can use the MARGE framework [108] to identify a set of cis -regulatory elements associated with differentially expressed genes. However, these approaches do not infer regulatory connections for individual genes.…”
Section: Integrative Approaches To Examine Cell-type Specific Regulatmentioning
confidence: 99%
“…In particular, it usually gives more reliable results to perform ChIP-seq data analysis in a quantitative manner, especially for cross-condition comparisons [8,9,16]. For example, several recent studies suggested to quantitatively combine the ChIP-seq signal intensity of a peak, sometimes called peak height, as well as the distance from this peak to a candidate target gene to represent its regulatory potential to the gene [16][17][18]. It has been shown that such a quantitative measure can integrate with other observations to better infer the functional impact of the protein's chromatin binding being studied.…”
Section: Introductionmentioning
confidence: 99%